Overview of emergency department visits due to concussion and the comorbidity of concussion and whiplash injuries in Iceland between 2010-2021 - Ólöf Jóhanna Sigurþórsdóttir 2000- (2023)
The incidence of concussions has received a lot of attention over the past years and numerous studies have been conducted on the topic. However, the majority of these studies are conducted on sport-related concussions, as well as many people do not seek medical help after sustaining a head injury. Furthermore, whiplash injuries often co-occur with concussions, but limited information is available on the comorbidity of such injuries. Thus, the epidemiology of these injuries in the general population is inadequate. Therefore, the study aimed to examine the frequency of ED visits at Landspitali between 2010 to 2021 due to concussions. The aim was also to examine the frequency of the comorbidity of concussion and whiplash injury. A Chi-square test was used to examine differences between age and gender. A total of 10,725 ED visits were due to concussion, of those, 872 had a comorbid whiplash injury. The main findings suggest that not enough people visit the ED after sustaining a concussion in Iceland. The results of the study can provide important information on the epidemiology of concussions and the comorbidity of concussion and whiplash injury in the Icelandic population. Keywords: Concussion, mild traumatic brain injury, whiplash-injuries, emergency department, general population Tíðni heilahristings hefur vakið mikla athygli undanfarin ár og hafa fjölmargar rannsóknir verið gerðar á heilahristing. Hins vegar eru flestar rannsóknir gerðar á íþróttatengdum heilahristing, auk þess sem margir leita sér ekki læknishjálpar eftir að hafa fengið höfuðáverka. Jafnframt, gerast hálsáverkar oft samhliða heilahristings en takmarkaðar upplýsingar eru til um slík meiðsli. Faraldsfræði heilahristings og hálsáverka sem skeður samhliða heilahristings hjá almenningi er því ófullnægjandi. Þess vegna var markmið rannsóknarinnar að bera kennsl á tíðni koma á bráðamóttökuna á Landspítalanum á árunum 2010 til 2021 vegna heilahristings. Einnig var markmiðið að kanna tíðni hálsáverka sem gerast samhliða heilahristings. Kí-kvaðrat próf ...